Development of a two-step high-resolution melting (HRM) analysis for screening sequence variants associated with resistance to the QoIs, benzimidazoles and dicarboximides in airborne inoculum of Botrytis cinerea. Issue 2 (1st November 2014) - Chatzidimopoulos, Michael; Ganopoulos, Ioannis; Vellios, Evangelos; Madesis, Panagiotis; Tsaftaris, Athanasios; Pappas, Athanassios C.
Abstract: A rapid, high-resolution melting (HRM) analysis protocol was developed to detect sequence variations associated with resistance to the QoIs, benzimidazoles and dicarboximides in Botrytis cinerea airborne inoculum. HRM analysis was applied directly in fungal DNA collected from air samplers with selective medium. Three and five different genotypes were detected and classified according to their melting profiles in BenA and bos1 genes associated with resistance to benzimidazoles and dicarboximides, respectively. The sensitivity of the methodology was evident in the case of the QoIs, where genotypes varying either by a single nucleotide polymorphism or an additional 1205-bp intron were separated accurately with a single pair of primers. The developed two-step protocol was completed in 82 min and showed reduced variation in the melting curves' formation. HRM analysis rapidly detected the major mutations found in greenhouse strains providing accurate data for successfully controlling grey mould. HRM analysis is a very sensitive method allowing to detect mutation-based fungicide resistance. HRM analysis is a very sensitive method allowing to detect mutation-based fungicide resistance.